Optimalisasi Pelayanan Administrasi Sebagai Upayameningkatkan Kepuasan Masyarakat - Handayani, Wiwik; Askafi, Eka (Universitas Islam Kadiri, 2025)
This study aims to describe the ef orts made in optimizing administrative services deliveredbyPATEN of icers, public satisfaction with administrative services delivered by PATENof icers, and factors that influence public satisfaction with administrative services deliveredbyPATEN of icers at the Prambon District Of ice, Nganjuk Regency. This study usesaqualitative approach with a descriptive research type. Primary data in this studywereobtained by observation techniques, Focus Group Discussions, and interviews. Secondarydata were obtained by documentation techniques. The data were analyzed descriptivelywithvalidity techniques using source and technique triangulation. The results of the study indicatethat the ef orts made in optimizing administrative services delivered by PATENof icers areby:(1) implementing PATEN services in accordance with the requirements statedintheRegulation of the Minister of Home Af airs Number 4 of 2010 and in accordance withtheSOP and directions from the Sub-district Head; (2) fulfilling the requirements for PATENservice operators according to the type of service, namely serving the public whosubmit requests for friendly, agile and responsive services to help people who are still experiencingdif iculties; (3) implementing PATEN systems, mechanisms and procedures that are clear andwell fulfilled; (4) completion times that are in accordance with the provisions or inatimelymanner; (5) determining the amount of service fees or rates determined based on what hasbeen agreed upon so as to avoid the practice of extortion; (6) producing good PATENservicetype specification products, namely in terms of making requests for population documents andpermits easily and quickly; (7) increasing the competence of implementers so that theycanserve the public more professionally; (8) handling complaints, suggestions and input well;and (9) completing facilities and several infrastructure that increasingly provide comfort forthe public as PATEN users. Public satisfaction with the administrative services providedbypublic service of icers as PATEN of icers at the Prambon Sub-district Of ice, NganjukRegency, is in the Very Good category. Factors influencing public satisfactionwithadministrative services provided by public servants as of icers of PATEN at the PrambonSub-district Of ice, Nganjuk Regency, include the PATEN service implementers or operators;the systems, mechanisms, and procedures of the PATEN service; the time requiredtocomplete the PATEN service; the costs/tarif s applied to the PATEN service; the product specifications of the PATEN service type; the competence and behavior of PATENserviceimplementers; the handling of complaints, suggestions, and input on the PATENservice; andthe facilities and infrastructure of the PATEN service.